Mantle cell lymphoma: involvement of nodal and extranodal sites in the head and neck, with multifocal oral lesions - Marcucci, Marcelo; Marcucci, Gilberto; Cordeiro, Mirna Scalon; León, Jorge Esquiche; Araujo, Juliane Piragine; Oliveira, Jefferson Xavier de; Santos, Karina Cecília Panelli (Autopsy and Case Reports, 2017)
Mantle cell lymphoma (MCL) is a malignant B-cell neoplasm, which comprises monomorphic and small- to medium-sized mantle zone-derived lymphoid cells. It is characterized by chromosomal translocation t(11;14)(q13;q32) and CCND1 truncation, resulting in cell cycle deregulation. It is an aggressive type of non-Hodgkin lymphoma with a propensity to present with extranodal involvement. This study shows the case of an 80-year-old Caucasian male who complained of a 2-month progressive swelling on the right side of his face. The magnetic resonance imaging exam showed multifocal involvement of the head and neck, including oral manifestations, bilateral parotid glands, palate, tongue, and floor of the mouth. An incisional biopsy of the tumor mass was performed. The morphological and immunophenotypic findings were consistent with the diagnosis of MCL. The patient died 4 months later, without any chance of undergoing a therapeutic approach. Although MCL is a rare condition, it should be subjected to a differential diagnosis when affecting the maxillofacial area. Imaging exams and both immunohistochemical and morphological analyses are needed to reach the correct diagnosis. Here, we present an unusual MCL with multifocal involvement of the head and neck